An Insight to the Plants of Sacred Groves Used for Toxicological Treatment in Ayurveda - Maya, R.; Sanjai, V. N. (Indian Forester, 2023)
Sacred groves are the miniature of forest derived on the basis of cultural faith. These virgin areas have been protected since ages by traditional societies and indigenous communities with their own experiences and followed a system of cultural worship. Such ecosystem approaches have worked under certain rules and myths goes to be at the origin of temple. And those sacred places have great vegetation without any significant disturbance and thereby exhibit unidentified relatives of cultivated plant species and threatened species have great medicinal value.